The Dual Targeting of FcRn and FcγRs via Monomeric Fc Fragments Results in Strong Inhibition of IgG-Dependent Autoimmune Pathologies - Monnet, Céline; Jacque, Emilie; de Romeuf, Christophe; Fontayne, Alexandre; Abache, Toufik; Fournier, Nathalie; Dupont, Gilles; Derache, Delphine; Engrand, Anais; Bauduin, Aurélie; Terrier, Aurélie; Seifert, Alexander; et al. (Frontiers in Immunology, 2021)
Novel molecules that directly target the neonatal Fc receptor (FcRn) and/or Fc gamma receptors (FcγRs) are emerging as promising treatments for immunoglobulin G (IgG)-dependent autoimmune pathologies. Mutated Fc regions and monoclonal antibodies that target FcRn currently in clinical development hold promise for reducing the levels of circulating IgG. Additionally, engineered structures containing multimeric Fc regions allow the dual targeting of FcRn and FcγRs; however, their tolerance needs to be first validated in phase I clinical studies. Here, for the first time, we have developed a modified monomeric recombinant Fc optimized for binding to all FcRns and FcγRs without the drawback of possible tolerance associated with FcγR cross-linking. A rational approach using Fc engineering allowed the selection of LFBD192, a Fc with a combination of six mutations that exhibits improved binding to human FcRn and FcγR as well as mouse FcRn and FcγRIV. The potency of LFBD192 was compared with that of intravenous immunoglobulin (IVIg), an FcRn blocker (Fc-MST-HN), and a trimeric Fc that blocks FcRn and/or immune complex-mediated cell activation through FcγR without triggering an immune reaction in several in vitro tests and validated in three mouse models of autoimmune disease.